Canadian perspectives in multiple myeloma on the use of steroids in clinical practice based on patient and healthcare provider interviews - McKenzie, Farah; Gazzé, Gabriel; Hewitt, Joanne; Kolm, Kari; Pollock, Debra; Rowland, Suzanne; Crosbie, Tina (Frontiers in Oncology, 2022)
Corticosteroid (steroid) medications are associated with challenging adverse effects that can negatively impact patient quality of life. However, owing to a long legacy of effective use in treatment protocols, they remain a cornerstone of multiple myeloma (MM) care. We conducted a roundtable with Canadian healthcare providers (HCPs) with diverse healthcare backgrounds and involvement in MM care as well as with patients with MM. Our goal was to develop clear guidance for steroid management aimed at improving patient quality of life, taking into account patient perspective and experiences with managing the disease. Our recommendations, which are based on the insights acquired from this discussion, can be categorized to the following areas: steroid prescribing, dosing, and modifications; managing adverse effects; and patient-HCP communication. These recommendations can be used by the entire multi-disciplinary hematology team to improve patient quality of life while being treated with steroid medication for multiple myeloma.